Organized screening programmes for breast and cervical cancer in 17 EU countries: trajectories of attendance rates - Maria Michela Gianino; Jacopo Lenzi; Marco Bonaudo; Maria Pia Fantini; Roberta Siliquini; Walter Ricciardi; Gianfranco Damiani (BMC, 2018)
Abstract Background The aim was to analyse participation trajectories in organised breast and cervical cancer screening programmes and the association between socioeconomic variables and participation. Methods A pooled, cross-sectional, time series analysis was used to evaluate secondary data from 17 European countries in 2004-2014. Results The results show that the mammographic screening trend decreases after an initial increase (coefficient for the linear term = 0.40; p = 0.210; 95% CI = − 0.25, 1.06; coefficient for the quadratic term = − 0.07; p = 0.027; 95% CI = − 0.14, − 0.01), while the cervical screening trend is essentially stable (coefficient for the linear term = 0.39, p = 0.312, 95% CI = − 0.42, 1.20; coefficient for the quadratic term = 0.02, p = 0.689, 95% CI = − 0.07, 0.10). There is a significant difference among the country-specific slopes for breast and cervical cancer screening (SD = 16.7, p < 0.001; SD = 14.4, p < 0.001, respectively). No association is found between participation rate and educational level, income, type of employment, unemployment and preventive expenditure. However, participation in cervical cancer screening is significantly associated with a higher proportion of younger women (≤ 49 years) and a higher Gini index (that is, higher income inequality). Conclusions In conclusion three messages: organized cancer screening programmes may reduce the socioeconomic inequalities in younger people's use of preventive services over time; socioeconomic variables are not related to participation rates; these rates do not reach a level of stability in several countries. Therefore, without effective recruitment strategies and tailored organizations, screening participation may not achieve additional gains.